Diabetic kidney disease surveillance among Type-2 Diabetes Mellitus patients in Kuantan, Pahang - Abdullah, Fa’iza; Kamaluzaman, Qamarul Azwan; A. Rahman, Nor Azlina; Md Aris, Mohd Aznan (2022)
Diabetic Kidney Disease (DKD) is the leading cause of chronic kidney disease (CKD) and end-stage renal failure word wide (1), associated with increased morbidity and mortality. It increases the economic burden and greatly impacts individuals, families and the government financially. DKD develops in 40% of patients with type 2 diabetes mellitus (T2DM) and 30% with type-1 diabetes. The increasing prevalence of DKD parallels the dramatic rise of T2DM. There is no cure for diabetic kidney disease, but treatments achieving blood sugar levels under control can delay or stop the progression of the disease.